Reduced Graphene Oxide Coated Silk Fabrics with Conductive Property for Wearable Electronic Textiles Application. (18th February 2019) - Zulan, Liu; Zhi, Li; Lan, Cheng; Sihao, Chen; Dayang, Wu; Fangyin, Dai
Abstract: The desire for this lightweight and flexible electronics has grown increasingly, and the flexible and wearable electronic textiles can be realized by coating traditional textiles with conductive materials. Here, the conductive silk fabrics are prepared by coating graphene oxide (GO) onto silk fabrics and followed by thermal reduction. The scanning electron microscope results show that the GO coated onto silk fabrics successfully forms a continuous thin film. The oxygen functional groups are removed by thermal reduction. The main structure (β‐sheet structure) of silk fabrics is not destroyed through a series of treatment, guaranteeing good mechanical properties. The resistivity and conductivity of silk fabrics using regenerated silk fibroin as a glue can reach 3.28 KΩ cm −1, 3.06 × 10 −4 S cm −1 respectively, which can meet the electron conductive requirement of wearable electronics. Thus, it can be used for sensors, portable devices, and wearable electronic textiles. Abstract : Conductive silk fabrics are prepared by coating graphene oxide onto silk fabrics using regenerated silk fibroin (RSF) as glue, following by thermal reduction. These materials possess flexibility, good mechanically properties, and thermal stability. Along with their conductivity this makes them ideal materials for advancing sensors, portable devices, wearable electronic textiles, and even biomedical devices.